A case study on the effect of Empty Fruit Bunch (EFB) and compost on oil palm plantation yield at Ladang LKPP Pulau Manis, Pahang / Nur Qurratuaini Mohd Najib - Mohd Najib, Nur Qurratuaini (Faculty of Plantation and Agrotechnology, 2018)
The aim of this study was conducted to determine the effect of applications (EFB and Compost) on oil palm yield from 2012 to 2016 (5 years) and to compare which applications were the best to apply at Ladang LKPP Pulau Manis, Pahang. Secondary data was obtained from Ladang LKPP Pulau Manis and analyzed by using Minitab software with One-Way ANOVA calculation method. From the result, it clearly shows that the mean yield productions in 2012 until 2016 (5 years) that have been applied with EFB were slightly and constantly higher compared to the yield production with compost with the total mean 113.31 mt/ha and 97.24 mt/ha, respectively. The highest yield of oil palm production applied with EFB was 26.2 mt/ha (2014) and the lowest was 18.5 mt/ha (2016). Compost in 2014 showed the highest yield 22.48 mt/ha while in 2016 indicated the lowest yield with 17.15 mt/ha. The results were analyzed with One-Way ANOVA and it showed that there was significant difference (P-value 0.032<0.05) between yield production of EFB and compost solely in 2015. The remaining years showed no significant. The results from this secondary data suggested that application of EFB is more efficient and give slightly high yield of oil palm production at Ladang LKPP Pulau Manis, Pahang. However, further data is needed for meaningful recommendation.